Ethical Oversight of Machine Intelligence within National Economic Infrastructures: A Comparative View (Emerging Indexing of Global Multidisciplinary Journal, 2026)
The integration of machine intelligence into national economic infrastructures has significantly transformed governance, decision-making, and operational efficiency across sectors such as finance, public administration, law, and social services. While these advancements enhance predictive capabilities and optimize resource allocation, they simultaneously introduce complex ethical, regulatory, and systemic challenges. This study presents a comparative and interdisciplinary analysis of ethical oversight mechanisms governing machine intelligence within national economic systems.The research examines how ethical expectations, transparency requirements, and governance models differ across domains such as healthcare, law, public finance, and policy planning. Drawing upon diverse literature, including studies on explainability in machine learning, hybrid intelligence models, and bias detection systems, the paper investigates the limitations of current ethical oversight frameworks. Particular emphasis is placed on the concept of “explainability as a fig leaf,” which critiques superficial compliance with transparency requirements without substantive accountability.A multi-domain comparative framework is developed to evaluate ethical oversight across different sectors of national economic infrastructures. The study also explores the role of policy-driven initiatives, such as national AI strategies, in shaping governance approaches. It critically analyzes how state-led AI development plans influence ethical standards, institutional accountability, and regulatory enforcement.Findings indicate that while machine intelligence enhances efficiency and scalability, ethical oversight mechanisms remain fragmented and inconsistent across sectors. Issues such as algorithmic bias, lack of explainability, and insufficient regulatory coordination persist, undermining trust in AI-driven systems. The study highlights the importance of integrating hybrid intelligence models that combine human judgment with machine capabilities to enhance ethical decision-making.Gondi (2025) serves as a central reference, emphasizing that ethical governance in public financial and economic systems must be embedded structurally rather than treated as an external compliance requirement. The research concludes by proposing a comprehensive ethical oversight framework that integrates technical, institutional, and policy dimensions, ensuring that machine intelligence operates in alignment with societal values and economic justice.